Invasion of Native Riparian Forests by Acacia Species Affects In-Stream Litter Decomposition and Associated Microbial Decomposers - Pereira, Ana (2021)
The invasion of native riparian forests by exotic tree species can lead to profound changes in the ecological integrity of freshwater ecosystems. We assessed litter decomposition of native (Alnus glutinosa and Quercus robur) and invasive (Acacia melanoxylon and Acacia dealbata) tree species, and associated microbial activity and community structure, after being immersed for conditioning in 3 reference and 3 “invaded” streams in Serra da Lousã (central Portugal) and used in microcosms simulating stream conditions. Litter decomposition differed among species, in the order: Al. glutinosa > Q. robur > (Ac. melanoxylon ~ Ac. dealbata). Alnus glutinosa litter decomposed faster probably because it was soft and had high nitrogen concentration for decomposers. Quercus robur litter decomposed slower most likely because it was tough and had high polyphenol and low nitrogen concentrations. Acacia melanoxylon litter was the toughest and had a thick cuticle that likely acted as a physical barrier for microbial colonization. In Ac. dealbata, the small-sized leaflets and high lignin concentration may have limited microbial litter decomposition. Litter decomposition was faster in “invaded” streams, probably because they were N-limited and increases in nitrogen concentration in water, promoted by Acacia species invasion, stimulated microbial activity on litter. The aquatic hyphomycete community structure differed among litter species and between stream types, further suggesting that microbes were sensitive to litter characteristics and water nutrient concentrations. Overall, the invasion of native riparian forests by Acacia species may affect microbial decomposer activity, thus altering important stream ecosystem processes, such as litter decomposition and nutrient cycles.